High-responsivity hybrid α-Ag2S/Si photodetector prepared by pulsed laser ablation in liquid - Ismail, Raid A.; Rawdhan, Hanan A.; Ahmed, Duha S. (Beilstein Journal of Nanotechnology, 2020)
We report the synthesis of α-Ag2S nanoparticles (NPs) by one-step laser ablation of a silver target in aqueous solution of thiourea (Tu, CH4N2S) mixed with cationic cetyltrimethylammonium bromide (CTAB) as surfactant. The effect of the CTAB surfactant on the structural, morphological, optical, and elemental composition of Ag2S NPs was evaluated using X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and UV–vis spectroscopy. The optical absorption decreased and the optical energy gap of α-Ag2S increased from 1.5 to 2 eV after the CTAB surfactant was added to the Tu solution. XRD studies revealed that the synthesized Ag2S NPs were polycrystalline with a monoclinic structure and that crystallinity of the nanoparticles was improved after adding CTAB. Raman studies revealed the presence of peaks related to Ag–S bonds (Ag modes) and the longitudinal optical phonon 2LO mode. Scanning electron microscopy investigations confirmed the production of monodisperse Ag2S NPs when using the CTAB surfactant. The optoelectronic properties of α-Ag2S/p-Si photodetector, such as current–voltage characteristics and responsivity in the dark and under illumination, were also improved after using the CTAB surfactant. The responsivity of the photodetector increases from 0.64 to 1.85 A/W at 510 nm after adding CTAB. The energy band diagram of the α-Ag2S/p-Si photodetector under illumination was constructed. The fabricated photodetectors exhibited reasonable stability after three weeks of storage under ambient conditions with a responsivity of 70% of the initial value.
Keywords: cetyltrimethylammonium bromide (CTAB); laser ablation; monodisperse; photodetector; silver(I) sulfide (Ag2S); thiourea